A Bibliometric Analysis of Similarity Attraction Bias in Recruitment: Implications for Workplace Diversity and Inclusion - Andreea BUNICA (Revista de Management Comparat International)
The effect of similarity attraction bias on hiring procedures and workplace diversity is examined in this paper. It looks at how cognitive biases, such favoring people who are similar to oneself, affect hiring practices and maintain inequalities in diversity in businesses. The study summarizes important ideas, such as gender, race, and organizational culture, by combining theoretical understandings and actual data from a thorough literature review. The research landscape is mapped using a bibliometric analysis with VOSviewer, which highlights important keywords and thematic clusters pertaining to diversity, bias, and recruiting. The study highlights significant patterns and relationships in the literature, keeping the focus on the psychological, organizational, and demographic elements which affect diversity results. This paper emphasizes topics for further study and theoretical developments. Simultaneously, it offers useful insights based on both theoretical and data-driven viewpoints to organizations looking to improve their diversity and inclusion efforts.